Treatment of hallux rigidus with percutaneous arthrodesis: a case series - Nogueira, Vitor Baltazar; Pereira Filho, Miguel Viana; Mattos e Dinato, Mauro Cesar; Freitas, Márcio de Faria; Pagnano, Rodrigo Gonçalves (Scientific Journal of the Foot & Ankle, 2018)
Objective: The objective of this study was to describe the percutaneous arthrodesis technique with single medial portal of the first metatarsophalangeal joint and to evaluate the results of a series of nine cases (10 feet) with a diagnosis of hallux rigidus subjected to this technique, comparing the results with literature data regarding the conventional technique. Methods: This was a retrospective, observational study performed by analysis of medical records and radiographs of nine patients undergoing percutaneous arthrodesis of the hallux metatarsophalangeal joint. Gender, age, consolidation time, level of postoperative pain and degree of patient satisfaction were evaluated. Results: Eight patients were female, and one patient was male. The mean age was 68.7 years, the mean consolidation time was 8 weeks, the consolidation ratio was 70%, there was pain improvement in the postoperative period, and all patients considered themselves satisfied with the surgery. Conclusion: Percutaneous arthrodesis of the metatarsophalangeal hallux joint potentially yields results similar to those of the conventional method demonstrated in the literature but uses smaller incisions. Level of Evidence IV, Therapeutic Studies, Case Series.